Schwenckia aurantiaca (Solanaceae), a new species from calcareous outcrops of northern Minas Gerais, Brazil - Paucar, Jenny Olga Arrea; Stehmann, João Renato (Phytotaxa, 2021)
A new species of Schwenckia (Solanaceae) from calcareous outcrops of the Serra Azul Biological Reserve in northern Minas Gerais, Brazil, is described and illustrated. Schwenckia aurantiaca is an annual plant characterized by a cylindrical corolla tube with five orange, linear appendages, an androecium with two stamens and three, unequal pilose staminodes, and a calyx that tears to the base in fruit. We discuss the morphological characters, habitat, and conservation status of the species, which is assessed as Critically Endangered.